ANALISIS KESULITAN MEMBACA PADA SISWA KELAS 4 DI SEKOLAH DASAR NEGERI 62 BANDA ACEH - Ziba, Fara; Aswita, Dian; Julia, Putry (Jurnal Seramoe Education, 2024)
he aim of this research is to determine the factors that influence the reading difficulties of grade 4 students at SDN 62 Banda Aceh. This research uses a qualitative descriptive research method. Researchers collected data using observation techniques to find out directly the causes of reading difficulties in class 4B at State Elementary School 62 Banda Aceh and interviews were conducted to obtain more detailed information from teachers and students regarding reading difficulties. The results of this research show that there are two factors that cause students to experience learning difficulties, namely internal and external factors. Observation results show that internal factors faced by students include students lacking concentration and not understanding the learning being taught, students not wanting to participate in the lesson. Students are not comfortable communicating with teachers and friends. Meanwhile, the results of interviews with students showed that students showed difficulty in understanding text, recognizing words and associating sounds with letters. External factors that influence students' reading difficulties are problems within the student, including learning disorders such as dyslexia, lack of exposure to reading activities at home, or inappropriate teaching methods.